TEKNIK PENILAIAN DIRI BERBASIS GOOGLE FORM PADA MATA PELAJARAN FIKIH DI MADRASAH TSANAWIYAH - Sundara, Hadmi; Handayani, Yeni; Perdana Putri, Desi Nursyifa; Latipah, Euis (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The study aims to investigate and optimize the implementation of self-assessment techniques in Islamic Education classes at MTs Assa’idiyyah by utilizing Google Forms. The Indonesian national education objectives, as outlined in the Constitution of the Republic of Indonesia in 1945, emphasize the enhancement of societal intellectualism through a conscious and planned educational system. However, traditional self-assessment practices face challenges, such as limited time, excessive workload, and the need for substantial resources. The integration of Google Forms offers an efficient and effective alternative, aligning with the principles of objective, integrated, economical, transparent, accountable, and educative assessments. The research methodology employs a qualitative approach involving interviews, observations, and document analysis. MTs Assa’idiyyah is the chosen unit of analysis, characterized by its adoption of the 2013 curriculum, adequate facilities, and previous absence as a research subject. The findings reveal that traditional self-assessment practices encounter limitations, motivating the exploration and implementation of Google Forms for self-assessment. The Google Forms-based self-assessment optimally adheres to the principles of assessment, offering objectivity, integration, efficiency, transparency, accountability, and educative aspects. The study concludes with the positive impact of Google Forms-based self-assessment on ninth-grade students, demonstrating disciplined and routine self-assessment practices, high-interest levels, and the formation of personal character. Moreover, teachers at MTs Assa’idiyyah can execute self-assessment authentically and objectively. The findings advocate for the widespread adoption of Google Forms as a valuable tool to enhance the effectiveness of self-assessment practices in Islamic Education